Characterization of Hydrogel Beads Based on Sodium Alginate and Bacterial Cellulose as Encapsulants for Red Palm Oil Emulsion (Elaeis guineensis Jacq) - Fitri Zuzilla Maha Rilmi; Ira Desri Rahmi; Deivy Andhika Permata (Journal of Fibers and Polymer Composites, 2026)
Red palm oil is a carotenoid-rich lipid source with functional potential, but its bioactive compounds are susceptible to oxidative degradation during processing and storage. This study aimed to develop red palm oil emulsion hydrogel beads using sodium alginate and bacterial cellulose as encapsulating materials and to evaluate the effect of their ratios on physicochemical and encapsulation properties. Beads were prepared by emulsion ionotropic gelation using CaCl₂ as a crosslinking agent. A completely randomized design with five treatments and three replications was used, and data were analyzed by ANOVA followed by Duncan’s New Multiple Range Test at a 5% significance level. The sodium alginate-to-bacterial cellulose ratio significantly affected yield, bead size, sphericity factor, swelling capacity, total carotenoid content, and encapsulation efficiency. Increasing bacterial cellulose proportion improved bead yield, diameter, carotenoid retention, and encapsulation efficiency. Treatment E, containing 50 mL sodium alginate, 25 mL bacterial cellulose, and 25 mL red palm oil emulsion, showed the best characteristics, with 63.17% yield, 3.55 mm bead size, 0.004 sphericity factor, 44.47 µg/g total carotenoid content, and 83.21% encapsulation efficiency. These findings indicate that sodium alginate–bacterial cellulose hydrogel beads are promising encapsulants for carotenoid-rich red palm oil emulsion.